2015
DOI: 10.3402/rlt.v23.28507
|View full text |Cite
|
Sign up to set email alerts
|

The space for social media in structured online learning

Abstract: In this paper, we explore the benefits of using social media in an online educational setting, with a particular focus on the use of Facebook and Twitter by participants in a Massive Open Online Course (MOOC) developed to enable educators to learn about the Carpe Diem learning design process. We define social media as digital social tools and environments located outside of the provision of a formal university-provided Learning Management System. We use data collected via interviews and surveys with the MOOC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 25 publications
1
45
1
2
Order By: Relevance
“…Hosted by the free CourseSites (Blackboard™) Learning Management System (LMS), the CD MOOC utilised online activities, known as e‐tivities (Salmon, ), light touch e‐moderation (Salmon, ), group collaboration, and digital badges to lead participants towards completion. Aspects of the CD MOOC such as academic professional development, digital badging and the use of social media in a structured online learning were reported elsewhere (Lokuge Dona, Gregory, & Pechenkina, 2016; Lokuge Dona, Gregory, Salmon, & Pechenkina, ; Salmon, Gregory, et al ., 2015; Salmon, Ross, Pechenkina, & Chase, ).…”
Section: The Carpe Diem Mooc: Intent Planning and Broad Outcomesmentioning
confidence: 99%
“…Hosted by the free CourseSites (Blackboard™) Learning Management System (LMS), the CD MOOC utilised online activities, known as e‐tivities (Salmon, ), light touch e‐moderation (Salmon, ), group collaboration, and digital badges to lead participants towards completion. Aspects of the CD MOOC such as academic professional development, digital badging and the use of social media in a structured online learning were reported elsewhere (Lokuge Dona, Gregory, & Pechenkina, 2016; Lokuge Dona, Gregory, Salmon, & Pechenkina, ; Salmon, Gregory, et al ., 2015; Salmon, Ross, Pechenkina, & Chase, ).…”
Section: The Carpe Diem Mooc: Intent Planning and Broad Outcomesmentioning
confidence: 99%
“…Twitter has been used to connect peers and share information, such as resources or comments on their personal and real-time status (Lin, Hoffman, & Borengasser, 2013). Facebook was found to have a greater impact than Twitter (Alario-Hoyos, Pérez-Sanagustín, Delgado Kloos, & Munoz-Organero, 2014;Salmon, Ross, Pechenkina, & Chase, 2015), and also more useful according to MOOC learners (Liu et al, 2016). MOOC learners also reported that the social networking tools had a positive impact on the social aspects of their learning process (Brownell & Swaner, 2010;Dodge & Kendall, 2004;Kassens-Noor, 2012) but they preferred to use the social medium to which they were already accustomed (Veletsianos & Navarrete, 2012).…”
Section: Tools For Interactionmentioning
confidence: 99%
“…Student's perception regarding social media platforms as being beneficial and useful in their studies that lead them to collaborate and integrate with others through these sites to share resources available to them [14]. Another study revealed that some of the students agreed that social media like Facebook was helpful to their collaborative learning [21]. Overall, we argue that when students use social media for academic use, they increase the use of collaborative learning.…”
Section: Academic Purpose and Collaborative Learningmentioning
confidence: 99%